Application of a new choline-imidazole based deep eutectic solvents in hybrid magnetic molecularly imprinted polymer for efficient and selective removal of naproxen from aqueous samples - Husin, Nor Aniisah; Muhamad, Musthahimah; Yahaya, Noorfatimah; Miskam, Mazidatulakmam; Nik Mohamed Kamal, Nik Nur Syazni; Asman, Saliza; Raoov, Muggundha; Mohamad Zain, Nur Nadhirah (Elsevier, 2021)
A magnetic molecularly imprinted polymer (Fe3O4@MIP) with naproxen (as template) was successfully prepared by adding a co-solvent consisting of a choline-imidazole based deep eutectic solvent (ChCl-BuIM) during polymerisation. The morphological, functional group, and magnetic characteristics of the synthesised materials were characterised by elemental analysis, Fourier transform-infrared spectroscopy, scanning electron microscopy, and vibrating sample magnetometer. This hybrid Fe3O4@MIP-ChCl-BuIM material was used as a magnetic adsorbent for efficient and selective removal of naproxen from wastewater samples. A batch adsorption study showed that adsorption of naproxen onto the multilayer surface of the adsorbent through a chemisorption mechanism. The data showed that the adsorption was feasible, spontaneous, and exothermic. The Fe3O4@MIP-ChCl-BuIM removed more naproxen (93.2–97.1%) than Fe3O4@MIP without ChCl-BuIM (83.2–88.9%). This finding confirms that the use of ChCl-BuIM improved both the selectivity and affinity of the MIP adsorbent towards naproxen. Competitive recognition studies of the Fe3O4@MIP-ChCl-BuIM using naproxen and structurally similar non-steroidal anti-inflammatory drugs revealed that the Fe3O4@MIP-ChCl-BuIM had high selectivity for naproxen. A cytotoxicity test showed that the synthesised ChCl-BuIM was non-toxic, as the human normal cell lines MCF-10A, and BEAS-2B maintained viability above 50%. These results show that Fe3O4@MIP-ChCl-BuIM has potential for use as a functional adsorption material for the removal of naproxen from water samples.